The Effects Analysis of Transformational Leadership, Work Motivation and Compensation on Employee Performance in PT. Sago Nauli - Purba, Kuras; Sudibjo, Kusman (Budapest International Research and Critics University, 2020)
This study aims to describe the effect of transformational leadership, work motivation and compensation on the performance of employees of PT. Sago Nauli. This research was conducted at PT. Sago Nauli which lasts for 5 (five) months, starting from October 2019 to February 2020. This research uses proportional random sampling method. The population in this study were all employees of PT. Sago Nauli palm oil mill totaling 180 people. The respondents of this study were determined using the slovin formula which numbered 124 (one hundred twenty four) people. The instrument used was a questionnaire to collect data from transformational leadership variables, work motivation, compensation and employee performance variables. Data analysis techniques used are validity test, reliability test, descriptive analysis, multicollinearity test, normality test, heterokedasticity test, multiple linear regression analysis, partial hypothesis test or t test, simultaneous hypothesis test or F test, and calculation of the coefficient of determination. Descriptive analysis results for transformational leadership variables, work motivation, compensation variables and employee performance are in the good category at PT. Sago Nauli. Based on partial analysis, transformational leadership, work motivation, compensation has a positive and significant effect on employee performance at PT Sago Nauli. Simultaneously, transformational leadership, work motivation and compensation have a positive and significant influence on employee performance at PT. Sago Nauli. The contribution of transformational leadership variables, work motivation, and compensation explained the employee performance variable of 0.760 or 76%. The remaining 0.240 or 24% is influenced by other independent variables not examined in this study.